THE ROLE OF THE NIAS LANGUAGE IN STRENGTHENING SCIENCE CONCEPTS WITHIN A LOCAL CULTURAL CONTEXT IN SENIOR HIGH SCHOOL - Darmawan Harefa (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to examine the use of the Nias language as a medium for strengthening science (Physics) concepts in Grade X at SMA Negeri 1 Teluk Dalam within the context of local culture. The research focuses on how integrating local language can improve students’ understanding of abstract physics concepts, particularly motion and force. A mixed-method approach was applied, combining quantitative data from pretest and posttest results with qualitative data from observations, questionnaires, and interviews. The findings show that students who learned physics using the Nias language achieved higher learning outcomes compared to those who used conventional instruction. The use of local language made learning more contextual, meaningful, and easier to understand. It also increased students’ motivation, participation, and confidence during the learning process. Furthermore, students were able to relate physics concepts to their daily life experiences and cultural environment. This study concludes that the integration of the Nias language in physics learning is an effective strategy to improve conceptual understanding and scientific literacy while preserving local cultural identity. Therefore, culturally based learning approaches should be considered in science education to enhance both academic achievement and cultural awareness among students.